Pajak E-Commerce, Pemecahan dan Solusinya - Ajat Sudrajat (Jurnal Pajak Vokasi (JUPASI), 2020)
Electronic or e-trade trading (English: Electronic Commerce, also e-commerce) is a spread, purchase, sales, marketing goods and services through an electronic system such as internet or television, www, or other computer networks. Ecommerce can involve electronic fund transfers, electronic data exchange, auto inventory management systems, and automatic data collection systems. The Information Technology industry sees this e-commerce activity as the application and application of e-business (e-business) related to commercial transactions, such as: electronic fund transfer, SCM (E-Marketing), e-marketing), online marketing, online transaction processing (online transaction processing), electronic data interchange / edi), etc.E-commerce is part of e-business, where e-business coverage is wider, not just a commerce but includes also co-entrance business partners, customer service, job vacancies etc. Seeing very fast developments of the e-commerce growth in the world including in Indonesia, it is necessary an effective strategy for the tax authority in the reacting. One of the things that need to be concern is this very rapid growth should be maintained so that there is no distortion as a result of taxation policy. During this time, the tax aspect in e-commerce has been the highlight of tax authorities in the world, especially whether there should be a new tax impression on this transaction and also how to align the existing tax rules with e-commerce development.Transactions through digital media or e-commerce in Indonesia need rebuilding from the side of the legislation (Cyberlaw) so that in the future do not miss the dispute in it runs. This happens because the difficulty of tracking the transactions used through the e-commerece is either B-to-B (business to business) or B-to-C (business to consumers). For example the relationship between the supplier with the factory, how the apparatus is to oversee the existence of transactions or not between the two through the e-commerce the solution of solving the problem is the government must take steps in solving the unstable internet infrastructure issues and frequent reliable transportation, the licensing procedure of customs to dedicate to the duty procedure from dawn to the negative trade for the other value to increase the efficacy to make the rules for the epimal services that are still under the regulations of the same bank as well as the public of the transactions of online transactions, plan and conduct the introduction of certification systems, a number of large players should be able to open the way of foreign investment, including doing some major plans for foreign investors, of course with clear regulations and the government must provide ease of rules for small and medium business to gain access to investors, and giving taxes to the company in the new company.